1981
DOI: 10.1098/rspa.1981.0002
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of fluid flow resulting from the impact of a water drop with an unyielding dry surface

Abstract: The flow of fluid associated with the impact of water drops of radius R at a speed V onto unyielding dry metal surfaces of known roughness R a is described. Spatial dimensions of the deforming drop are normalized by transformations of the kind x ' — x/R , and time scales are normalized according to t ' = tV/R , to permit comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(115 citation statements)
references
References 0 publications
8
104
1
Order By: Relevance
“…A rich body of literature already exists considering perpendicular drop impacts, with a droplet falling from above onto a flat surface [1][2][3][4][5][6][7][8]. These studies have revealed the underlying mechanics and possible outcomes of droplet splashing and are industrially relevant to processes such as spray coating, spray cooling and inkjet printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rich body of literature already exists considering perpendicular drop impacts, with a droplet falling from above onto a flat surface [1][2][3][4][5][6][7][8]. These studies have revealed the underlying mechanics and possible outcomes of droplet splashing and are industrially relevant to processes such as spray coating, spray cooling and inkjet printing.…”
Section: Introductionmentioning
confidence: 99%
“…For droplet impacts at a normal angle of incidence, the threshold of the onset of splashing (K) has traditionally been defined using the Weber number, = 2 / , and the Reynolds number, = / , with μ the dynamic viscosity of the liquid. The splashing threshold (K) has been shown to follow the correlation [5,16]:…”
Section: Introductionmentioning
confidence: 99%
“…At even faster flow rates dripping transitions towards jetting, when the Weber number reaches a critical value [67]. Also, dripping and jet breakup induce longitudinal oscillations in the generated drops [68,69]. The frequency of these oscillations is controlled by surface tension and the mass of the drop [70], and viscous forces tend to dissipate these oscillations.…”
Section: Fluid Dynamics Descriptionmentioning
confidence: 99%
“…Area of Convergence, Directionality [13] [ 5,97] Area of Origin [13,19,68 Backspatter Pattern; Forward Spatter Pattern area of origin, weapon [48] [5, 47,110,191] Blood Clot [6,162] [ 160 , 162] Bloodstain pattern area of origin, weapon [13,35,76 [ 166,170,196] Perimeter Stain time between drip and wipe-off, [155,197,198] [ 155,188] [188] [155,163,197,198] Flow Pattern [12,162,199] [12, 162,185,199] [185] [12] Impact Pattern weapon, motion; directionality [78][79][80]128] [5] [72,128,136] Insect Stain [157,200] Mist Pattern weapon, directionality [81, 154 , 186 Spatter Stain [201] [126, [15...…”
Section: Mixingmentioning
confidence: 99%
“…Stow and Hadfield [6] studied the effects of surface roughness on spreading and splashing of water droplets and established that splashing was promoted by increasing drop diameter (D), impact velocity (V), and surface roughness (R a ). These droplet impact parameters were combined with the density (r), viscosity (m), and surface tension (s) of the liquid to give two non-dimensional groupings: the Reynolds number (Re ¼ rVD=m) and Weber number (We ¼ rV 2 D=s).…”
Section: Introductionmentioning
confidence: 99%